A check list of necrophagous flies (Diptera: Calyptratae) from urban area in Medellín, Colombia (2012)
An updated checklist of necrophagous flies (Diptera, Calyptratae) occurring in the urban area of Medellín- Colombia is presented. 27 species belonging to 4 families are reported. Data were obtained from field work and recent bibliography references.